Sleep Monitoring Using WatchPAT Device to Predict Recurrence of Major Depression in Patients at High Risk for Major Depression Disorder Recurrence: A Case Report - Harlev, Daniel; Ravona-Springer, Ramit; Nuriel, Yonatan; Fruchter, Eyal (Frontiers in Psychiatry, 2021)
Background: Major depressive disorders are strongly correlated with alterations in sleep pattern and architecture, including changes in the Rapid Eye Movement (REM) phase. However, it is still unknown whether sleep alterations precede other depression-related symptoms, particularly in patients with recurrent depressive episodes at relapse risk. Case presentation: We initiated a study aimed at examining the value of ambulatory sleep monitoring using a WatchPAT device, in predicting recurrence of Major depression. Depression was assessed monthly with the Beck Depression Inventory version II (BDI-II). Here we present the case of a 63 years old woman, with a history of recurrent depressive episodes. AT the time of recruitment, she was asymptomatic, she experienced recurrence of Major depression 3 months into the study. We observed a significant reduction of the Rem Latency parameters five weeks prior to BDI-II score increase, reflecting major depressive episode recurrence. Conclusion: Though our results are preliminary, they suggest that ambulatory sleep monitoring can be used as a simple and accessible tool, predicting recurrence of Major Depressive episodes in patients at high risk, thus enabling early treatment intervention.